2019
DOI: 10.3892/etm.2019.7431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application value of brain CT perfusion imaging in the treatment of acute ischemic stroke thrombolytic therapy

Abstract: Clinical application value of CT perfusion (CTP) imaging in the treatment of acute ischemic stroke (AIS) thrombolytic therapy was investigated. Retrospective analysis of 185 suspected AIS patients in Liaocheng Brain Hospital from April 2012 to December 2017 were involved. We observed the non-contrast CT (NCCT) and CTP in the diagnosis of AIS patients, and recorded as well as compared CTP parameters of AIS patients. The National Institute of Health Stroke Scale (NIHSS) rating was conducted, and the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…A large number of reports showed that CTP related parameters can detect cerebral ischemic injury in the early stage and could provide an effective basis for clinical diagnosis and treatment decision [30,31]. Decreased CBF may indicate that cerebral circulation reserve is decompensated, and even further develops into cerebral infarction [32]. A previous study found that core infarct volume was associated with clinical prognostic indicators on the 14th and 90th day, which further reinforced our results [33].…”
Section: Discussionsupporting
confidence: 88%
“…A large number of reports showed that CTP related parameters can detect cerebral ischemic injury in the early stage and could provide an effective basis for clinical diagnosis and treatment decision [30,31]. Decreased CBF may indicate that cerebral circulation reserve is decompensated, and even further develops into cerebral infarction [32]. A previous study found that core infarct volume was associated with clinical prognostic indicators on the 14th and 90th day, which further reinforced our results [33].…”
Section: Discussionsupporting
confidence: 88%
“…CT perfusion is a strong diagnostic modality for accurate assessment of volumetric core/penumbra mismatch ratios, thus predicting the volume of potentially rescuable tissue at risk that can be saved from recanalization therapy [ 17 , 18 ]. It not only aids in the selection of stroke patients for reperfusion treatment but also has good prognostic value [ 19 ]. CT may not only help in the selection of candidates for endovascular intervention in conjunction with tPA therapy, but it can also help in those patients in whom the use of tPA is contraindicated [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTP has been widely used in patients with AIS and can evaluate ischemic penumbra visually [36,37]. CTP has the advantages of relative rapidity and wide applicability [38,39]. In addition to CTP, some studies have reported the diagnostic value of magnetic resonance imaging (MRI) in AIS [40][41][42][43].…”
Section: Advantages Of Ctp and Its Potential For Detecting Htmentioning
confidence: 99%